2017
DOI: 10.3126/jmcjms.v5i1.17989
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm production in relation to extended spectrum beta-lactamase production and antibiotic resistance among uropathogenic Escherichia coli

Abstract: Not available. Janaki Medical College Journal of Medical Sciences (2017) Vol. 5(1): 61-63

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
3
2
0
Order By: Relevance
“…Among 60 E. coli isolates, 31.66% were strong biofi lm producers, 21.66% moderately positive, 21.66% were weak ones and 25% were biofi lm non-producers by using microtitre plate method which were in accordance with the fi ndings of Neupane et al (2016) and Khatri et al (2017).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Among 60 E. coli isolates, 31.66% were strong biofi lm producers, 21.66% moderately positive, 21.66% were weak ones and 25% were biofi lm non-producers by using microtitre plate method which were in accordance with the fi ndings of Neupane et al (2016) and Khatri et al (2017).…”
Section: Discussionsupporting
confidence: 77%
“…The overall prevalence of E. coli in urine samplesfrom UTI suspected patients was15% (60/400). Neupane et al (2016) and Khatri et al (2017) showed very similar report of 15.5% and 14.1% respectively. In this study the prevalence of UTI by E. coli was higher in female population than in male population which was statistically signifi cant (p<0.05) which is consistent with many other studies.…”
Section: Discussionsupporting
confidence: 63%
“…The previous studies of Neupane et al, (2016); Khatri et al, (2017) confirmed the low prevalence of E. coli isolates recovered from urine samples of UTI suspected patients. Basically, the usual diagnosis of UTI is based on a quantitative estimation of bacteria in urine culture that yield greater than 10 5 cfu/ ml (Kass, 1957).…”
Section: Epidemiologysupporting
confidence: 67%
“…(Abernethy et al 2017). Resistance to ciprofloxacin was significantly higher in developing countries (Ethiopia -85.5%, Nepal -64.6%, Pakistan -60.8%, Mongolia -58.1%, Jordan -55.5%) (Ali et al 2016, Khatri et al 2017Munkhdelger et al 2017;Regasa Dadi et al 2018;Shakhatreh et al 2018) than in developed countries (USA -5.1%, Germany -10.5%, Switzerland -17.4%, France -24.8%) (Lavigne et al 2016;Erb et al 2018;Hitzenbichler et al 2018;Yamaji et al 2018). The study conducted in Switzerland showed also that patient age over 65 years was associated with higher E. coli resistance to ciprofloxacin (Erb et al 2018).…”
mentioning
confidence: 98%